A model proposition for strategies definition in manufacture processes improvement in reference to its environment impact - Espinosa, Fernando; Salinas, Gonzalo (Rev. Téc. Fac. Ing. Univ. Zulia)
The model in this paper has its origin in the analogy between the degradation that suffers the energy in any transformation and the degradation that it suffers the environment for effect of the industrial activities, in anyone of its stages, this is in the natural resources extraction, in the transformation activity and in those poured of mass residuals and energy. It outlines a form of generating efficiency indicators in the transformation process, keeping in mind the contamination variable. Their bases are in thermodynamic principles, in systems analysis and in simulation models.